Percutaneous‐transhepatic‐endoscopic rendezvous procedures are effective and safe in patients with refractory bile duct obstruction. Issue 3 (1st April 2019) - Bokemeyer, Arne; Müller, Friederike; Niesert, Hannah; Brückner, Markus; Bettenworth, Dominik; Nowacki, Tobias; Beyna, Torsten; Ullerich, Hansjörg; Lenze, Frank
Abstract : Background: Percutaneous‐transhepatic‐endoscopic rendezvous procedures (PTE‐RVs) are rescue approaches used to facilitate biliary drainage. Objective: The objective of this article is to evaluate the safety and the technical success of PTE‐RVs in comparison with those of percutaneous transhepatic cholangiographies (PTCs). Methods: Percutaneous procedures performed over a 10‐year period were retrospectively analyzed in a single‐center cohort. Examinations were performed because of a previous or expected failure of standard endoscopic methods including endoscopic retrograde cholangiography (ERC) or balloon‐assisted ERC to achieve biliary access. Results: In total, 553 percutaneous procedures including 163 PTE‐RVs and 390 PTCs were performed. Overall, 71.3% of the patients suffered from malignant disease with pancreas‐carcinoma (32.8%) and cholangio‐carcinoma (19.0%) as the most frequent, while 28.7% of the patients suffered from benign disease. Many patients had a postoperative change in bowel anatomy (50.8%). PTC had a higher technical success rate (89.7%); however, the technical success rate of PTE‐RVs was still high (80.4%; p  < 0.003). Overall complications occurred in 23.5% of all procedures. Significantly fewer complications occurred after performing PTE‐RVs than after PTCs (16.6% vs 26.4%; p  = 0.037). Conclusion: Beside a high technical efficacy of PTE‐RVs, significantly fewer complications occur following PTE‐RVs than following PTCs; thus, PTE‐RV should be preferred over PTC alone in selected patients.